IMPLEMENTASI TRILOGI EPISTEMOLOGI ILMU PERSPEKTIF ABED AL-JABIRI DALAM PENGEMBANGAN PEMIKIRAN PENDIDIKAN ISLAM - Wirdatul Hasanah; Asnawan; Titarini (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to examine and analyze the implementation of Abed al-Jabiri’s epistemological trilogy—bayani, burhani, and irfani—in the development of Islamic education. Epistemology plays a crucial role in shaping an educational system because it determines how knowledge is acquired, validated, and developed. In practice, Islamic education has often been dominated by a textual approach (bayani), which tends to limit the development of critical reasoning and spiritual depth. Therefore, an integrative approach that combines bayani, burhani, and irfani is needed to enable Islamic education to respond effectively to the challenges of modernity characterized by rapid scientific and technological advancement. This research employs a qualitative method with a library research approach, examining the works of Abed al-Jabiri and relevant literature on epistemology and Islamic education. The findings indicate that the implementation of Al-Jabiri’s epistemological trilogy can be realized through integrative curriculum development, critical-reflective learning methods, and the enhancement of educators’ competencies. The bayani approach strengthens textual understanding, burhani fosters rational and scientific thinking, and irfani nurtures spiritual values and moral character. The balanced integration of these approaches is expected to produce a holistic and adaptive model of Islamic education.